EEG Findings in Posterior Reversible Encephalopathy Syndrome. (September 2019) - Murray, Kathleen; Amin, Ushtar; Maciver, Stephanie; Benbadis, Selim R
Introduction . Posterior reversible encephalopathy syndrome (PRES) is a relatively common cause of encephalopathy in the hospital setting, and the EEG findings have not been well described. The purpose of this study was to review the EEG findings in a series of patients with PRES. Methods . We retrospectively reviewed our electronic medical record database to identify patients who received a diagnosis of PRES at Tampa General Hospital from January 2016 to October 2017. The diagnosis of PRES was suspected on clinical presentation and confirmed by magnetic resonance imaging. We selected patients with PRES who had received at least 1 EEG. EEGs were interpreted by 2 board-certified electroencephalographers. Results . From January 2016 to October 2017, 19 patients were diagnosed with PRES at Tampa General Hospital. Of those, 10 received at least 1 EEG. Four patients were male, 6 were female. The ages ranged from 21 to 87 (mean was 47). The patients had the following clinical presentations: 5 with encephalopathy, 8 with seizures, 2 with vision changes, and 3 with headache (some patients had more than 1 symptom). EEGs findings were as follows: 3 were normal; 3 showed intermittent generalized slowing; 2 showed continuous generalized slowing; 3 showed background slowing; 1 showed background suppression; 1 showed generalized rhythmic delta activity (GRDA); 1 showed GRDA, plus spike/sharp-wave discharges; 1 showed generalized periodic discharges. The etiologies were as follows: 9 from hypertension, 1 secondary to eclampsia, 3 due to posttransplant immunosuppression, and 1 patient was undergoing chemotherapy (some were multifactorial). Conclusion . EEG findings in PRES are diverse, with no specific or even predominant pattern, based on this small sample size.